Chylothorax diagnosis: can the clinical chemistry laboratory do more?. (January 2015) - Gibbons, Stephen M; Ahmed, Farhan
Background: Chylothorax is a rare anatomical disruption of the thoracic duct associated with a significant degree of morbidity and mortality. Diagnosis usually relies upon lipid analysis and visual inspection of the pleural fluid. However, this may be subject to incorrect interpretation. The aim of this study was to compare pleural fluid lipid analysis and visual inspection against lipoprotein electrophoresis. Methods: Nine pleural effusion samples suspected of being chylothorax were analysed. A combination of fluid lipid analysis and visual inspection was compared with lipoprotein electrophoresis for the detection of chylothorax. Results: There was 89% concordance between the two methods. Using lipoprotein electrophoresis as gold standard, calculated sensitivity, specificity, negative predictive value and positive predictive value for lipid analysis/visual inspection were 83%, 100%, 100% and 75%, respectively. Conclusion: Examination of pleural effusion samples by lipoprotein electrophoresis may provide important additional information in the diagnosis of chylothorax.